The existence of insider trading in Malaysia: an event study approach - Yusof, Abdul Hafiz; Mohd Nasarudin, Ahmad Fawwaz; Haris, Sharazad; Muhamad Yusuf, Noor Hafizha; Wan Zakaria, Wan Mohd Farid (Universiti Teknologi Mara ( Perlis), 2013)
This paper focuses on the role of insider trading activity in Malaysia. It attempts to indicate the existence of the abnormal profit from this activity. Recently developed countries like United States and United Kingdom have reported that the activity can no longer gives abnormal profit for long period due to laws imposed in those countries, attention now turns to emerging market like Malaysia. By using event study analysis, 200 cases of insider trading activity reported between January 2008 and March 2009 were closely examine and the result shows that while abnormal return do exist, it is mostly not significant. This paper also looks at the individuals and institutional insider and their performances respectively.